Pemberian Kompos Daun Lamtoro dan Pupuk Organik Cair BiotoGrow untuk Meningkatkan Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays L. saccharata) - Rusli Rusli; Farida Hariani; Aisyah Lubis (Jurnal Agrofolium, 2023)
The goal of this research was to find out how much sweet haagung (Zea mays L. saccharata) growth and yield might be boosted by using lamtoro leaf compost in combination with biotogrow liquid organic fertilizer (POC), and how those two factors interacted with one another. The experimental setup was a randomized factorial block design with 2 components and 3 replications, the first of which was the application of lamtoro leaf compost (L), with its own 3 levels of variation. namely L0 = no treatment (control). L1 = 2 kg plot-1. L2 = 4 kg plot-1. The second factor was the administration of liquid organic fertilizer (POC) biotogrow (B) consisting of 4 levels. namely B0 = no treatment (control). B1 = 1.5 ml L-1 of water. B2 = 3 ml L-1 of water and B3 = 4. 5 ml L-1 of water. The height of the plants, husk diameter, and cob weight were measured in centimeters, centimeters, and grams, respectively. The study found that the variable of plant height responded strongly to the addition of lamtoro leaf compost. has a highly substantial impact on the cob weight per plot but a negligible impact on the cob diameter measure. Biotogrow liquid organic fertilizer (POC) showed a considerable impact on plant height characteristics after being applied. increased the average plot weight of cob husks but had no appreciable impact on husk diameter. All measured parameters were unaffected by the combination of the two fertilizers.